Between virtual and real: exploring hybrid interaction and communication in virtual worlds. (2016) - Christopoulos, Athanasios; Conrad, Marc; Shukla, Mitul
In this paper we aim to explore the potential advantages of interactions on student engagement and provide guidance to educators who seek interactive and immersive learning experiences for their students through the use of hybrid virtual learning approaches. We define as hybrid virtual learning the educational model where students are co-present and interacting simultaneously both within a virtual world and the physical classroom receiving stimuli related to the learning material in the virtual world from both directions. In order to achieve our aim, we categorised interactions in various categories and observed the complex network of interactions which can be developed in a virtual world when groups of people are working together in order to achieve different goals. The findings suggest that students spontaneously tend to use the interaction channels only when it is deemed to be necessary.